IMPLEMENTASI PRINSIP KONSEP RESTORATIVE JUSTICE PADA PELAKSANAAN DIVERSI (STUDI KASUS DI D. I. YOGYAKARTA) - Nur Anisah, Laili; Hastarini, Arvita (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
The concept of restorative justice is the basis for implementing diversion in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Diversion is presented to prevent children in conflict with the law from the bad excesses of the criminal justice system and return the condition of children, victims and communities to the state they were in before the crime occurred. However, based on data from the Indonesian Child Protection Commission (KPAI), criminal acts committed by children continue to increase every year. This research aims to see whether the concept of restorative justice is achieved or not in the implementation of diversion. The problem studied is whether the implementation of diversion is by the principles of restorative justice seen from the cases studied. If it is not by the principles of restorative justice, are there other alternatives so that the principles of restorative justice are fulfilled? The research used an empirical approach by examining 7 cases of child diversion spread across the Yogyakarta City Police and Sleman Police. Cases were analyzed using 3 principles and 4 values of restorative justice coined by Van Ness and Strong. The results of this research concluded that 5 out of 7 cases did not meet the criteria for the restorative justice concept, the rest did. Other methods are needed that can facilitate the implementation of the principles of restorative justice, namely the approach of the perpetrator's family to the victim's family before implementing diversion, the influence of the victim's parents in the diversion process, and mutually agreed compensation.